Candidate gene associations reveal sex‐specific Graves' disease risk alleles among Chinese Han populations. Issue 7 (27th April 2020) - Yan, Chen‐Yan; Ma, Yu‐Ru; Sun, Feng; Zhang, Rui‐Jia; Fang, Ya; Zhang, Qian‐Yue; Wu, Feng‐Yao; Zhao, Shuang‐Xia; Song, Huai‐Dong
Abstract: Background: With several susceptibility single nucleotide polymorphisms identified by case–control association studies, Graves' disease is one of the most common forms of autoimmune thyroid disease. In this study, we aimed to determine whether any observed differences in genetic associations are influenced by sex in Chinese Han populations. Methods: A total of 8, 835 patients with Graves' disease and 9, 936 sex‐matched healthy controls were enrolled in the study. Confirmed by a two‐staged association analysis, sex‐specific analyses among 20 Graves' disease susceptibility loci were conducted. Results: A significant sex‐gene interaction was detected primarily at rs5912838 on Xq21.1 between the GPR174 and ITM2A genes, whereby male Graves' disease patients possessed a significantly higher frequency of risk alleles than their female counterparts. Interestingly, compared to women, male patients with Graves' disease had a higher cumulative genetic risk and higher persistent thyroid stimulating hormone receptor antibody‐positive rate after receiving antithyroid drug therapy for at least 1 year. Conclusion: The findings of this study suggest the existence of one potential sex‐specific Graves' disease variant on Xq21.1. This could increase our understanding of the pivotal mechanism behind Graves' disease and ultimately aid in identifying possible therapeutic targets. Abstract : In this study, sex‐specific genetic differences in Graves' disease have been reported by expanding a recent GWAS of GD to include the X chromosome. The most significant sex‐gene interaction was observed at rs5912838 on Xq21.1, and male patients with Graves' disease had a higher cumulative genetic risk by calculating weighted genetic risk scores (wGRSs).